Bimbingan Kelompok dalam Membantu Perencanaan Studi Lanjut Siswa Kelas XII MAN 2 Kuningan (Altruism: The Indonesian Journal of Community Engagement, 2024)
The high interest of Madrasah Aliyah students to continue their education to a higher level is still constrained by confusion in choosing a study program due to lack of further study information or career information, problems regarding costs, and problems with parents. Ideally, every class XII student should have careful planning so that they can determine the steps after completing their education to the next level according to their talents and interests. With the implementation of group guidance services, it is hoped that class XII students can exchange ideas about the importance of planning a career from an early age, and be able to foster enthusiasm in individuals to have plans for further studies or careers. This activity aims to help improve students' understanding and ability in planning careers or further studies. The method used is community education through group guidance. The subjects in this study were class XII students of MAN 2 Kuningan. The data collection technique is unstructured interview. The results of this community service activity showed that students' knowledge about further studies increased and some students began to be able to plan their further studies.Tingginya minat siswa Madrasah Aliyah untuk melanjutkan pendidikan ke jenjang yang lebih tinggi masih terkendala dengan kebingungan dalam memilih program studi dikarenakan kurangnya informasi studi lanjut atau informasi karir, adanya masalah perihal biaya, serta adanya persoalan dengan orang tua. Idealnya setiap siswa kelas XII harus memiliki perencanaan yang matang sehingga dapat menentukan langkah setelah menyelesaikan pendidikan menuju jenjang selanjutnya sesuai bakat dan minatnya. Dengan dilaksanakannya layanan bimbingan kelompok diharapkan siswa kelas XII dapat bertukar pikiran tentang pentingnya merencanakan karir sejak dini, dan mampu menumbuhkan semangat pada diri individu untuk memiliki recana dalam studi lanjut atau karir. Adapun kegiatan ini bertujuan untuk membantu meningkatkan pemahaman dan kemampuan siswa dalam merencanakan karir atau studi lanjutnya. Metode yang digunakan adalah pendidikan masyarakat melalui bimbingan kelompok. Subjek dalam penelitian ini adalah siswa kelas XII MAN 2 Kuningan. Teknik pengumpulan data adalah dengan wawancara tak terstruktur. Hasil dari kegiatan pengabdian kepada masyarakat ini menunjukkan bahwa pengetahuan tentang studi lanjut siswa bertambah dan sebagian siswa mulai mampu merencanakan studi lanjutnya.
Keywords: Bimbingan Kelompok; Studi Lanjut.